Analyzing the Self-Pay Benefits of Starting a Small Business - Sahtoni Sahtoni; Neng Sandra Fitriani Permata Hati; Nia Kurniati; Abu Muna Almaududi Ausat; Silvy Sondari Gadzali (Journal on Education, 2023)
A large number of people in the community are now running small businesses, which are discussed in this journal. The vast majority of people are self-employed, and small businesses have always been the foundation upon which larger enterprises have been built. The purpose of this study was to investigate the merits of working for oneself, specifically through the creation of a small business. Analyzing natural phenomena by way of qualitative research methods informed by post-positivism was the focus of this investigation. Since we ourselves are the primary research tool, authors employed a triangulation (combined) data collection method, drawing in part from interview and observational findings, and relying on inductive (qualitative) analysis to place more emphasis on specific meaning than broad generalizations. The results of this study show that although most respondents provided almost the same explanation and assessment of the value of digitization in the wholesale sector, namely avoiding unemployment, having a steady income, opening up job opportunities, and helping to increase family income.